Anthropometric and biochemical profile of adults who attended the “Programa de Educación y Atención Nutricional Universitario” of the University of Costa Rica, 2018-2019 - Valverde Vindas, Natalia (2024)
Introduction: obesity represents one of the main risk factors for the development of other metabolic and cardiovascular conditions. Knowing the anthropometric and biochemical profile of an individual allows the nutrition professional to optimize their care and focus their work not only on treatment but on the prevention of other possible associated comorbidities. Methodology: a cross-sectional and descriptive study was conducted with a quantitative methodological approach, with a data base of 196 nutritional files of adults, sociodemographic information, data on biochemical variables and anthropometric measures were analyzed. Results: 83.1 % of patients presented some degree of excess weight, 75 % high percentage of body fat, 52.6 % showed high risk of developing metabolic and cardiovascular diseases according to waist circumference. In addition, 83.67 % presented at least one of the lipid parameters outside normal limits and 25.51 % of patients had fasting hyperglycemia. Conclusion: the results obtained in the study agree with the national reality of the Costa Rican adult population, this may be associated with poor eating habits and lifestyle. Adult patients treated have nutritional problems such as overweight, obesity and alterations in the lipid and glycemic profile, which increases their cardiovascular and metabolic risk.